Trifluoropropyltrimethoxysilane 전해질 첨가제를 이용한 리튬이온전지의 싸이클 특성 향상 - 신원경; 박세미; 김동원; Shin, Won-Kyung; Park, Se-Mi; Kim, Dong-Won (전기화학회지, 2014)
In this study, we tried to improve the cycling performance of lithium-ion batteries by suppressing decomposition of the electrolyte solution containing fluorsilane-based additive. Trifluoropropyltrimethoxysilane was electrochemically oxidized and reduced prior to the decomposition of the liquid electrolyte composed of lithium salt and carbonate-based organic solvent. Thus, the stable solid electrolyte interphase (SEI) layer on both negative electrode and positive electrode was formed, and it was confirmed that the cycling performance of lithium-ion batteries assembled with electrolyte solution containing 5 wt.% trifluoropropyltrimethoxysilane was the mostly enhanced. The products formed on electrodes were analyzed by the SEM and XPS analysis, and it was demonstrated that trifluoropropyltrimethoxysilane can be one of the promising SEI-forming additives. 본 연구에서는 불소계 실란을 첨가제로 사용하여 전해액의 열화 반응을 억제함으로써 리튬이온전지의 싸이클 특성을 향상시키고자 하였다. 첨가제로 사용된 trifluoropropyltrimethoxysilane은 리튬염과 카보네이트계 유기 용매로 이루어진 액체 전해질보다 전기화학적 산화, 환원 분해반응이 먼저 일어나 음극 및 양극 표면에서 안정적인 고체전해질계면 (solid electrolyte interphase, SEI) 막을 형성하며, 5 wt.%의 첨가제를 포함하는 경우 가장 우수한 전기화학적 특성을 나타내었다. SEM 및 XPS 분석을 통해 전극 표면에 생성된 피막의 화학 성분을 분석하였으며, 이들 결과로부터 새로운 SEI 형성 첨가제로서 불소계 실란의 가능성을 확인하였다.